[Black speaker at University Union plaza podium] (1995)
The speaker is wearing a light blue suit. Closer to the foreground, three students are sitting on the stage to the left of the speaker, one is wearing a suit and red shoes. Two tall portable public address speakers are widely flanking the speaker. There are other people on the stage, behind the speaker, and there are a few students in the background.